Sustainable Economic Development through Capture Fisheries Downstreaming in Bone Regency - Marhati, Marhati; Hasnawati, Hasnawati; Masriadi, Masriadi; Yunus, Andi Muhammad; Muslimin, Muslimin (Universitas Medan Area, 2025)
This study examines the downstreaming strategies of capture fisheries products and their contribution to sustainable coastal economic development in Bone Regency, central Indonesia. Downstreaming is recognized as a critical approach to increasing value addition, diversifying income sources, and strengthening coastal communities’ welfare. A qualitative case study design was employed, involving 20 informants comprising fishermen, fish processing MSMEs, cooperatives, and local government officials. Data were collected through in-depth interviews, participatory observation, and policy documents review, and analyzed thematically using Miles and Huberman’s framework. The findings reveal six key aspects of downstreaming. First, post-harvest processing practices such as salted fish, fish flakes, crackers, and seaweed-based nuggets have significantly enhanced product value and reduced waste. Second, cooperatives and village-owned enterprises (BUMDes) act as aggregators and provide inclusive access to capital and markets. Third, infrastructure limitations, regulatory barriers, and low business literacy constrain market expansion. Fourth, downstreaming generates new opportunities for women and youth to engage in value chain and digital promotion. Fifth, multi-stakeholder synergy collaboration remains partial but has potential for formal institutionalization. Overall, the study underscores the need for integrated policies, institutional strengthening, and sustainable assistance to achieve inclusive, competitive, and environmentally friendly downstreaming of capture fisheries.